Optimering av råvarulager - Gustafsson, Fredrik; Lundqvist, Johannes (My University, 2014)
E2014:037, Material costs in process industries represent a significant part of organizations expenses. A desirable scenario is to utilize raw materials to their fullest potential, to minimize waste and to gain competitiveness. Provided products should correlate to customers’ demands to keep material costs to a minimum. A warehousing method that supports a vast amount of articles is required to push this ideal state whilst simultaneously offer flexibility to try out new articles in order to pursuit a competitive product. Stora Enso Packaging experienced that they were limited in their possibility to approach this state due to limitations in their warehousing regarding diversity in articles. The purpose of this report was to identify factors that prevented Stora Enso Packaging from increasing their number of supplied articles and to present solutions resulting in higher flexibility. Interviews were held with relevant people in order to get an overview of the situation. A greater understanding was achieved when data over delivery and consumption of raw materials from the year of reference 2013 was analyzed. This data were used to simulate how levels vary over time to identify where bottlenecks regarding article expansion were located. New layout proposals which support a greater amount of articles were presented and assigned area are supported by a simplified model of order point. A model over flexible warehousing was presented in order to meet the purpose of the thesis. Furthermore were changes regarding work routines presented which should result in a well-functioning warehousing.
Keywords: Övrig industriell teknik och ekonomi; Grundläggande vetenskaper; Hållbar utveckling; Produktion; Transport; Other industrial engineering and economics; Basic Sciences; Sustainable Development; Production; Transport